Leishmaniose Cutanées À Ain Dfali, Aspects Épidémio-Cliniques Comparatifs De 132 Cas - EL Alaoui Zakaria; Amayour Abdelaziz; El Aasri Aziz; EL Kharim Khadija; El Belghyti Driss (European Scientific Journal, ESJ, 2017)
Since the end of the 19th century, cutaneous leishmaniasis (CL) has been regarded as a public health problem in our country, Morocco. The aim of this study is to describe the clinical and epidemiological profile and posttherapeutic evolution of patients with cutaneous leishmaniasis in the Ain Dfali’s health center. We carried out a study based on the use of records and the observation of patients with cutaneous leishmaniasis between January 2006 and December 2015. Also, we collected 132 cases of cutaneous leishmaniasis. The mean age of patients was 19.8 years with extremes from 6 months to 61 years. The sex ratio was 0.76 M / F. The mean duration of lesions was 1.6 months with extremes of 2 weeks to 10 months. Fall preponderance was noted (41.6%). The most frequent clinical appearance was that of a single ulcero-pulmonary nodule (61%) (71.9%) and was seated on the face (57.5%). The diagnosis was mentioned clinically and confirmed by direct parasitological examination. Glucantime® was the treatment of choice that was used intralesionally. The post-therapeutic evolution was favourable with almost a complete disappearance of lesions. This took place in a period varying from 3 to 8 weeks at the price of unsightly scars in 19 patients. Cutaneous leishmaniasis continues to pose a real public health problem in our country. The emergence of severe and resistant forms throughout the world should encourage the multiplication and strengthening of prophylactic measures.